Covid-19 vaccine: costs, pricing and management (Costos y Gestión, 2021)
While there is not either cure or effective treatment against COVID-19, vaccines arise as only viable option forthe world to come back to “normalcy”. Process of research & development, manufacturing and distribution ofCOVID-19 vaccine is highly complex. More than 150 vaccine candidates are now being developed through differentand indeed revolutionary technologies for having vaccines available by the end of 2020 or early 2021. Objective of this paper is to present a holistic assessment of management, costs and pricing for theCOVID-19 vaccine process, studying its whole value chain, including R&D, manufacturing, marketing anddistribution, but focusing on costing techniques and methodologies used by companies, always based ontheir manufacturing models and technologies. Our goal is to make contributions that could be useful forcompanies and governments on three main aspects: unit cost calculation introducing life-cycle costing approach,effective pricing decisions by pharmaceutical companies and efficient purchasing models implementationby governments.Scientific and technological challenge is huge. From management perspective, decision making process andexcellence in execution are key; demand for a collaborative and coordinated actions by all stakeholders is vitalto reach the goal of having an effective and safe vaccine that is widely accessed by everybody.
Keywords: COVID-19; Vaccine; Manufacturing; Costs; Prices